CHALLENGES FACED BY CAREER WOMEN IN BALANCING WORK AND HOME RESPONSIBILITIES: A SYSTEMATIC LITERATURE REVIEW - Heriani, Avira; Afdal, Afdal; Hariko, Rezki (STKIP Pesisir Selatan, 2024)
Career women, engaged in the professional world with strong skills and education, face unique challenges when they get married. In addition to focusing on their careers, they must also prioritize household duties. Their multitasking and time management skills are tested, and success in both roles often depends on support, especially from their spouse. A systematic review of previous literature suggests that a lack of multitasking ability, effective time management, and social support may hinder career women's performance in their dual roles. The results of this study provide a deeper understanding of career women's dual role dynamics, especially in the context of husband support, dual role conflict, and coping strategies. Husband support was shown to have a significant positive correlation with career women's success in carrying out dual roles, while the level of optimism was not directly related to such success. In addition, it can provide a deeper understanding of the challenges and opportunities faced by career women, as well as provide valuable insights for practitioners and policies to develop more effective strategies to support dual career management in various national contexts.